Students’ Sports Behavior in the Kahayan River Basin, Palangka Raya City - Harvianto, Yudo; Abdullah, Abdullah; Alamsyah, Iwan Noor (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Sports are movement activities carried out by a person. Sports is an activity that is needed by a person to maintain physical fitness, so that these activities can be carried out optimally. Individuals who have carried out sports activities should be appreciated and made a matter of course, because if humans have done physical activities by exercising which is also accompanied by maintaining a healthy lifestyle, then later it will shape the body to be fit and not easily attacked by diseases that make the body healthy. The purpose of this study is to find out about Student Sports Behavior in the Kahayan River Basin, Palangka Raya City. This study uses a descriptive quantitative method. A total of 278 students living in the Kahayan River watershed were used as samples. The data collection technique in this study is a questionnaire in the form of indirect communication assisted by filling out through google forms. The conclusion obtained from this study is that every day students do sports activities with a minimum duration of 30 minutes in the afternoon. The purpose of students doing sports activities every day is to maintain a healthy body. In addition, there are also sports facilities around their homes, so parents or families always motivate them to do sports activities, especially around the house. At school, the majority of students have participated in extracurricular activities and like to watch sports matches. However, sometimes students are lazy to do sports activities due to insufficient time due to their individual busyness.